Improving the specific capacity of nickel hydroxide nanocrystals via yttrium doping for application in hybrid supercapacitors. Issue 27 (18th June 2019) - Zhu, Yuanyi; An, Shengli; Cui, Jinlong; Qiu, Hengrui; Sun, Xuejiao; Zhang, Yongqiang; He, Wenxiu
Abstract : Herein, Y-doped Ni(OH)2 composites were successfully fabricated via a simple hydrothermal process. Abstract : Herein, Y-doped Ni(OH)2 composites were successfully fabricated via a simple hydrothermal process. The specific surface areas were significantly improved when Y 3+ ions were incorporated into the Ni hydroxide lattice. The Y-doped Ni(OH)2 electrode exhibited the remarkable specific capacity of 735.46 C g −1 at 1.5 A g −1 and ultrahigh rate performance with 71.36% capacity retention at 20 A g −1 . The optimum Y-doped Ni(OH)2 electrodes were further evaluated for application in an asymmetric supercapacitor, demonstrating the maximum energy density of 55.49 W h kg −1 at the power density of 843.31 W kg −1 as well as satisfying cycling performance with 85.8% retention after 7000 cycles.